LUCID SUITCASE - Heavener, Mia, 1978- (Book collections on Project MUSE., 2019)
"In 1939, everything changes for Anne Girl when outsider John Nelson grounds his sailboat on the shores, into Anne Girl's skiff, and into her life during a rare storm in the Alaskan fishing village of Nushagak. When Anne Girl and her mother, Marulia, find their skiff flattened by John's boat, Anne Girl decides she both hates and wants him. Thus begins a generational saga of strong, stubborn Yup'ik women living in a village that has been divided between the new and the old, the bluff side and the missionary side, the cannery side and the subsistence side"--